Congenitally Corrected Transposition of the Great Arteries: Mid-term Outcomes of Different Surgical Strategies - He, Xiaomin; Shi, Bozhong; Song, Zhiying; Pan, Yanjun; Luo, Kai; Sun, Qi; Zhu, Zhongqun; Xu, Zhiwei; Zheng, Jinghao; Zhang, Zhifang (Frontiers in Pediatrics, 2022)
Background Optimal management for congenitally corrected transposition of the great arteries (ccTGA) is controversial. We applied different surgical strategies based on individual variations in our single-centered practice over 10 years, aming to describe the mid-term results. Methods From January 2008 to June 2021, 90 patients with ccTGA were reviewed and grouped by three different surgical strategies: 41 cases with biventricular correction as biventricular group, 11 cases with 1.5 ventricular correction as 1.5 ventricular group, and 38 cases with Fontan palliation as univentricular group. The mean age at primary surgery was 41.4 ± 22.7 months. Patients were followed for mortality, complications, reoperation, cardiac function, and valve status. Results The median follow-up period was 5.1 years (range, 1.5–12.5 years). The overall 10-year survival and freedom from reoperation rate was 86.7 and 82.4%, respectively. There were 3 early deaths and 3 mid-term deaths in the biventricular group, while 2 early deaths and 1 mid-term deaths were reported in the univentricular group. Although 1.5 ventricular group presented no death and the fewest complications, we still found similar mortality (p = 0.340) and morbidity (p = 0.670) among the three groups. The bypass time, aortic-clamp time, and ICU stay length were the longest in the biventricular group, followed by the 1.5 ventricular group (p < 0.001). However, in mid-term follow-up, biventricular and 1.5 ventricular groups both showed excellent cardiac function and obvious improvement of tricuspid regurgitation (p = 0.008 and p = 0.051, respectively). Fontan palliation provided acceptable mid-term outcomes as well, despite a lower ejection fraction. Conclusion Satisfactory mid-term outcomes could be achieved for highly selected ccTGA patients using the whole spectrum of surgical techniques. Moreover, 1.5 ventricular correction, as a new emerging technique in recent years, might hold great promise in future practice.